2012
DOI: 10.4028/www.scientific.net/amm.226-228.1776
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Foam Agent in Lightweight Aggregate Concrete

Abstract: Different content of foaming agent in the lightweight aggregate concrete test, the apparent density and compressive strength of concrete assessment indicators. Studies have shown that, with the dosage increase, the variation of the apparent density of the concrete is first decreases and then increases when the content is 0.8kg/m3 dry apparent density minimum; as the foaming agent content continues to grow, dry apparent density continues to increase, but the magnitude of increase is less obvious. At this point,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…There is a good relationship between design density and fresh density, whereby the fresh density of control FC mixes were decreased as higher percentages of foam dosage were added. This condition has a similar agreement with previous researchers by Bing et al [ 8 ] and Wang and Tang [ 84 ], who reported that increasing the dosage of foam results in decreasing density of FC. Moreover, there is a good relationship between the stability and consistency of the control FC mixes’ density.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There is a good relationship between design density and fresh density, whereby the fresh density of control FC mixes were decreased as higher percentages of foam dosage were added. This condition has a similar agreement with previous researchers by Bing et al [ 8 ] and Wang and Tang [ 84 ], who reported that increasing the dosage of foam results in decreasing density of FC. Moreover, there is a good relationship between the stability and consistency of the control FC mixes’ density.…”
Section: Resultssupporting
confidence: 93%
“…However, the control FC shared the similar trend in mortar where the dry density was slightly higher than fresh density in ranges below 100 kg/m 3 . Additionally, this condition has a similar agreement with previous researchers Bing et al [ 8 ] and Wang and Tang [ 84 ], found that increasing dosage of foam results in decreasing density and compressive strength of FC.…”
Section: Resultssupporting
confidence: 91%
“…Since the aggregate type has a main role in the strength properties of concretes, some researchers have investigated the influence of different natural and industrial aggregates including fly-ash (Lo et al, 2007, Wasserman & Bentur, 1997Chi et al, 2003), pumice (Sari & Pasamehmetoglu, 2005;Libre et al, 2011), natural pozzolan (Mouli & Khelafi, 2008), organic lightweight aggregates (Cheng et al, 2012), waste materials (Mahmud et al, 2011), dredged silt (Wang et al, 2010) clay-blended sludge (Tay et al, 1991), slag (Thomas & Bremner, 2012), oil palm shell (Shafigh et al, 2010) and shale (Zhuang et al, 2013) on the mechanical properties of lightweight aggregate concretes. Other researchers like Kim et al (2013), Wang and Tang (2012), Hassanpour et al (2012) and Pan et al (2011) studied experimentally the strength and mechanical behavior of other types of light weight concretes such as autoclaved aerated concrete, foamed concrete and fiber reinforced concretes. For those regions that are placed on the earthquake-prone areas (like Iran), the use of light weight structural materials is of great importance to decrease the risk of hazards during the earthquake.…”
Section: Introductionmentioning
confidence: 99%